TEKS LONTAR KALA PURANA (KAJIAN FILOSOFIS, SIMBOLIS, DAN NILAI) - I Made Suweta (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2019)
Lontar Kala Purana is one of the classical literature in Bali. This Lontar is one of the Hindu texts containing stories about Sang Hyang Kala and Sang Hyang Panca Kumara and its relation to the implementation of the manusa yajna ceremony in Bali which is a sapuhlegernceremony namely pangruwatan ceremony for people born to wuku wayang. Based on a brief description of the background in front, there are several things that can be raised as the following meaning of Lontar Kala Purana?, and (3) what value found in Lontar Kala Purana? Based on the analysis carried out, the results of this study are as follows: (1) philosophically the text of Lontar Kala Purana contains the meaning of time majesty (Kala) which is the  ower/omnipotenceof God Almighty/Ida Sang Hyang Widhi Wasa, (2) symbolically the text of Lontar Kala Purana contains several meanings (teachings of leadership, warning, asuri sampad, and daiwi sampad, (3) values of ethics (respect for parents and tolerance).